Histopathological effects of ultraviolet radiation exposure on the ocular structures in animal studies -literature review - Niguse Hamba; Asfaw Gerbi; Solomon Tesfaye (Elsevier, 2021)
The transparent anterior segment of the human eye (cornea and lens), as well as neural retina, are the principal target of UV radiation for both acute and long-term exposure. The histopathological changes increased along with irradiation intensity and UVB exposure. The injuries caused by UV irradiation to the cornea are named photokeratitis which is characterized by exfoliation of the corneal epithelium. Both the corneal epithelium and endothelium (which cannot regenerate) are vulnerable to UV radiation. Increased UVB exposures go deeper through the corneal epithelial layer, causes damage to the antioxidant protective mechanism, resulting in injury to the cornea and other parts of the eye. The radiation that hits the lens is first filtered by the lens capsule and about 60% of the radiation is transmitted by the anterior capsule. The transmitted radiation induces apoptosis in the lens epithelial cells and thereafter the cortical fibers which contribute to the formation of lens cortical opacities, over time, the lens yellows and loses its transparency (cataract). Lens epithelial cells are responsible for maintaining much of the homeostasis of the underlying fibers. Although the amount of UV radiation reaching the retina in the adult eye is very low (1% UV below 340nm and 2% between 340-360nm), much enough to degenerate outer nuclear layer area of the retina. Shorter wavelength light also is the most hazardous it is known to generate reactive oxygen species in the retina. The photoreceptors and retinal pigment epithelium located in the posterior pole are particularly susceptible to this radiation. The retinal pigment epithelium is especially susceptible to oxidative stress because of its high light, oxygen tension, fluorophore, and membrane lipid levels. The main aim of this review was to provide a comprehensive overview of the histopathological effects of UV radiation on the eye (cornea, lens, and retina), and various oxidative stress injuries in the animal models. Furthermore, the depletion of the ozone layer over the last decades has increased the amount of UVB at the Earth's surface. Thus the health risks associated with UV radiation exposure on ocular structures are mainly outlined.